Breaking the traditional communication flow: exploration of social media opinion leaders in health - Mohamad, Emma; Ahmad, Abdul Latiff; Mohamed Salleh, Sabariah; Wan Sulaiman, Ummu Khadijah (2017)
Opinion leaders play an important role in mitigating health issues and are able to influence attitudes and health behaviors to a certain extent.However, in the world we are living today, individual health decision making no longer rely fully on doctor’s advice, but often persuaded by people or organisations deemed reliable and trustworthy.Interestingly, one does not have to have a medical degree to be seen as “reliable” or “trustworthy” in giving out medical advices. Computermediated-communication changes the way opinion leaders emerge in virtual communities, specifically in the context of health.Through increased access to both traditional and online media, people have a fair access to communication technology and therefore, our definition of opinion leaders have shifted from how we used to understand it through Lazarsfeld’s two-steps flow theory. In fact, the way opinion leaders operate via social media platform is very different from how it used to be through the traditional mass media.This paper will discuss on the characteristics of new media opinion leaders, particularly in the context of health, in hopes to learn new ways to promote health in future communication campaigns.